Application of Commercial and Backyard Poultry Geographic Information System Databases for the Identification of Risk Factors for Clinical Infectious Laryngotracheitis in a Cluster of Cases on the Delmarva Peninsula - Johnson, Y.J.; Colby, M.M.; Tablante, N.L.; Hegngi, F.N.; Salem, M.; Gedamu, N.; Pope, C. (International Journal of Poultry Science, 2004)
Between May 4, 1998 and June 26, 1998 one broiler flock and six roaster flocks, all contracting with the same poultry integrator were reported positive for clinical Infectious Laryngotracheitis. A three-part study applying both standard outbreak investigation techniques and GIS tools was implemented to determine prevalence, distribution and risk factors for ILT. A field investigation, a case-control study, and sero-prevalence survey were conducted. The case-control study used a sample of 7 case flocks and 14 control flocks from the affected integrator. Risk factors analyzed include proximity to: broiler-breeder flocks, backyard flocks and game bird facilities. A systematic-random sample of 168 flocks were selected for the seroprevalence study. Case flocks were 36.00 (95% C.I. 2.69, 481.21) times more likely to be located within 1 mile of a backyard than control flocks. The prevalence of sero-positive flocks was 57.1%. Flocks from the affected integrator were significantly older that those from other integrators. Increased flock age was significantly associated with negative titers for Newcastle Disease, Infectious Bronchitis, and Infectious Bursal Disease. The development of commercial and backyard poultry flock databases facilitated the quantification of the risk imposed by backyard flocks to local commercial flocks. Immunological status of the bird may be an important risk factor for clinical ILT and production systems with older birds that are not managed as "all-in-all-out" may be at much greater risk of clinical ILT and perhaps other infectious diseases.